Kajian Potensi Pembangkit Tenaga Listrik Mikrohidro (PLTMH) Indragiri Hulu - Wahyu Budi Kusuma (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2020)
Power plants with small-capacity water energy sources (micro hydro with a capacity of <1 MW) are very precisely developed to reach the electrical energy needs in remote or difficult to reach areas. The potential of micro hydro power plants (MHP) in Indonesia until now has not been maximally utilized because of limited information about data and the potential of MHP. Under these conditions, the government is in accordance with the mandate of Law No. 30/2007 on energy has given special attention to the use of Micro Hydro Power Plants (MHP), especially aimed at remote / underdeveloped areas. This research aims to examine the potential of micro-hydro power plants in terms of potential power generation and slope stability. The results of this study indicate that the potential for power generation in the study area is a maximum of 38.11 kW and a minimum of 11.92 kW. Slope stability condition is very good with a safety factor above 1.3.